2009
DOI: 10.4314/jasr.v8i2.43345
|View full text |Cite
|
Sign up to set email alerts
|

Utilization Of Improved Root And Tuber Crops Production Technologies Among Extension Agents (EAs) In Kogi-East Senatorial Zone Of Nigeria

Abstract: The utilization of improved Root and Tuber Crops Production Technologies among Extension

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This finding agrees with Akpoko (2014) who reported that large households positively and significantly influenced the adoption of recommended soil management practices in Kaduna state. In addition, Tokula et al (2018) found that household size had positive and significant influence with the technology acceptance of rice varieties, implying that, the more the household size, the higher the probability of accepting improved rice varieties. Finally, extension visit had negative T-value of -.005.…”
Section: Factors Influencing Rice Farmers' Participation In Farmer Fi...mentioning
confidence: 99%
“…This finding agrees with Akpoko (2014) who reported that large households positively and significantly influenced the adoption of recommended soil management practices in Kaduna state. In addition, Tokula et al (2018) found that household size had positive and significant influence with the technology acceptance of rice varieties, implying that, the more the household size, the higher the probability of accepting improved rice varieties. Finally, extension visit had negative T-value of -.005.…”
Section: Factors Influencing Rice Farmers' Participation In Farmer Fi...mentioning
confidence: 99%